Industry vs. Services: Long‑ and Short‑Run Growth Effects of FDI in Türkiye - Derya Hekim (European Scientific Journal, ESJ, 2026)
This paper investigates how the sectoral composition of foreign direct investment (FDI) shapes economic growth in Türkiye. Using quarterly data and an autoregressive distributed lag (ARDL) framework, two separate models are estimated: one relating output to FDI in industry and the other to FDI in services. Bounds test results indicate the presence of a long‑run cointegrating relationship in both specifications, allowing for a joint assessment of long‑ and short‑run effects. The industry model shows that domestic capital has a positive long‑run impact on output, while labour contributes negatively and industry‑related FDI exerts a negative and significant effect, suggesting limited or adverse growth spillovers from manufacturing FDI. By contrast, in the services model, both capital and services‑sector FDI have positive and significant long‑run coefficients, and services FDI emerges as a key driver of growth. Short‑run dynamics reveal hump‑shaped responses of output to sectoral FDI, with initial gains or disruptions followed by partial reversals, whereas the error‑correction terms are negative and highly significant, indicating reasonably fast convergence back to the long‑run equilibrium in both models. The findings highlight that the growth payoff from FDI in Türkiye depends critically on its sectoral allocation.